The crime and the silence confronting the massacre of Jews in wartime Jedwabne - Bikont, Anna (William Heinemann, 2015)
"The devastating story of Jedwabne, which was the basis of Jan Gross's controversial Neighbors (2001). Based on the author's encounters with witnesses, survivors, murderers, and their helpers between 2000 and 2004, The Crime and the Silence raises important questions about the responsibility of Poles for the Holocaust"-- Provided by publisher